BS EN 4165-027. Aerospace series. Connector, electrical, rectangular, modular. Operating temperature 175 °C continuous. Part 027. Rack and panel rear mounted plug for 2 and 4 modules, series 3. Product standard (2nd March 2023) - British Standards Institution,
No abstract available